Structural factors for public dental health services in Regional Health Care Network 13: an analysis of the Brazilian National Program for Improving Access and Quality of Primary Care - Lucila Brandão HIROOKA; Guilherme Vinícius CATANANTE; Hélio Souza PORTO; Maria do Carmo Gullaci Guimarães CACCIA-BAVA (Universidade Estadual Paulista, 2018)
Abstract Introduction The Brazilian National Program for Improving Access and Quality of Primary Care aims to induce the institution of processes that expand the capacity of federal, state and municipal administrations and Primary Care teams to offer services that ensure greater access and quality. Objective To identify the characteristics of infrastructure for the dental health care of the health units from the Regional Health Care Network 13, from the perspective of a health evaluation. Material and method This is a descriptive and cross-sectional study in which is used the Module V database of the External Evaluation instrument of 156 health units of this region that participated of the 2nd cycle of the referred program, which discuss the modality of the health teams, structure and environment of the dental office, the hours of operation, equipment, instruments and dental supplies. Result In general, the oral health units of this study have dental offices with good structural conditions and sufficient equipment and supplies to carry out clinical activities, except those for dental prostheses, possibly due to the permanence of this service in secondary care. However, they point out that advances in access and coverage by oral health services are still necessary. Conclusion Although the theme includes other studies and reflections, the present work may contribute to discussions about the present condition, and it is recommended the active participation of all the actors involved in the care, in the search for the qualification of oral health services in this region.